Excessive Hypocoagulation in Therapy with Warfarin within Polypharmacy: Using online database Multi-Drug Interaction Checker and Graphic “Time-Effect-Drug Administration” to Eliminate Adverse Drug Event (Case Report) - G. S. Krasnov; I. V. Kazancev (Рациональная фармакотерапия в кардиологии)
The purpose of this article is to demonstrate a new approach to polypharmacy management in ambulatory practice using as example a case report  of adverse drug event (ADE) in patient with atrial fibrillation and comorbidity. The patient had excessive polypharmacy level (11 drugs). Minor bleeding developed when using these  drugs (INR – 6.70). The analysis of drug interactions was performed at patient’s home by online database "Multi-Drug Interaction Checker" and  "Time-effect-drug administration" graphic. As a result of analysis, it was  described two  drug  interactions led to minor bleeding: warfarin+rosuvastatin, warfarin+amiodarone. It was found that the patient had not taken rosuvastatin before and it was first-time administration of rosuvastatin. Therapy was corrected, the causes and effects of ADE are eliminated. The drugs without proven benefit and known drug interactions were cancelled. There were no clinical signs of bleeding after correction and the last INR was 2.54.Combined using of "Multi-Drug Interaction Checker" and  "Time-effect-drug administration" graphic allowed to detect causal relationship between ADE and drugs initiating it and then to make a rational decision right at the patient’s home in a short time.